Esensi Manusia sebagai Makhluk Berseni dan Beragama - Yasin Surya Wijaya; Samsul Maarif (Universitas Gadjah Mada, 2021)
AbstractThis study is motivated by the gap between the disciplines of art and religion, which are generally considered separate and inseparable. This paper intends to prove that art and religion are actually complementary disciplines and humans cannot be separated between the two. This study aims to explain how the essence of human as a creature is religious, artistic, and religious also artistic at the same time. This study used qualitative research methods with informant data sources, places & events, and documents or archives. Data were collected using in-depth interviews, participatory observation, and document analysis. Interviews were aimed at 6 different religious figures from the IMP organization (Indonesia Merayakan Perbedaan), namely Islam, Christianity, Catholicism, Hinduism, Buddhism, and Believers. Observations are aimed at human activities of various religions in religion and art which are carried out offline and online. Document analysis is aimed at extracting data from books, journals and other literature. The validity of the data was tested by source triangulation and informant review techniques. Data were analyzed using interactive analysis techniques with data reduction, display, and verification procedures. The results of the study show that humans are actually creative creatures so that the emergence of religion and art cannot be separated from human creativity in seeking true truth. Humans have institutionalized religion while not for art, so that art and religion are not really to be contested. Artwork and religious worship are manifestations of the truth as a result of human reflection. The conclusion is that art and religion are institutions that are inseparable and complementary, which are essential for humans. AbstrakKajian ini dilatarbelakangi oleh adanya kesenjangan antara lembaga seni dan agama yang umumnya dianggap terpisah dan tidak dapat disatukan. Tulisan ini hendak membuktikan bahwa sejatinya seni dan agama menjadi disiplin yang saling melengkapi dan manusia tidak bisa lepas antara keduanya. Kajian ini bertujuan untuk menjelaskan bagaimana esensi manusia sebagai makhluk beragama, berseni, dan beragama sekaligus berseni. Kajian ini menggunakan metode penelitian kualitatif dengan sumber data informan, tempat & peristiwa, dan dokumen atau arsip. Data dikumpulkan dengan teknik wawancara mendalam, observasi partisipatif, dan analisis dokumen. Wawancara ditujukan pada 6 tokoh agama berbeda dari organisasi (IMP) Indonesia Merayakan Perbedaan yaitu Islam, Kristen, Katolik, Hindu, Budha, dan Penghayat Kepercayaan. Observasi ditujukan pada aktifitas manusia dari berbagai agama dalam beragama dan berseni yang dilakukan secara offline maupun online. Analisis dokumen ditujukan untuk mengali data yang bersumber dari buku, jurnal, dan literatur lainya. Keabsahan data diuji dengan teknik triangulasi sumber dan review informan. Data dianalisis dengan teknik analisis interaktif dengan prosedur reduksi data, display, dan verifikasi. Hasil kajian menunjukan bahwa manusia sejatinya adalah makhluk kreatif sehingga munculnya agama dan seni tidak lepas dari kreativitas manusia dalam upaya mencari kebenaran sejati. Manusia telah melembagakan agama sedangkan tidak untuk seni, sehingga seni dan agama sejatinya tidak untuk dipertentangkan. Karya seni dan ibadah agama merupakan manifestasi kebenaran hasil renungan manusia. Kesimpulanya adalah bahwa seni dan agama menjadi lembaga yang keduanya tidak dapat dipisahkan dan saling melengkapi juga dibutuhkan manusia secara esensial.